PROBLEMS OF THE IMPLEMENTATION OF MEDIATION OF COPYRIGHT DISPUTES (Study at the Regional Office of the Ministry of Law of Central Java) - Aifa Saputri; Ubaidillah Kamal (Law Research Review Quarterly, 2026)
This study aims to analyze the problems of copyright dispute mediation implementation and their impact on dispute resolution effectiveness at the Regional Office of the Ministry of Law of Central Java. The main issue examined is the low mediation success rate despite mediation being mandated as the primary alternative dispute resolution mechanism before litigation. This study employs a qualitative descriptive method with an empirical juridical approach through in-depth interviews with officials and mediators, analysis of mediation case documents, and review of relevant laws and regulations. The analysis applies Soerjono Soekanto's Legal Effectiveness Theory, encompassing five determining factors: legal substance, law enforcement, facilities and infrastructure, society, and legal culture. Results indicate that during 2023 to 2025, only two of six mediated copyright disputes reached agreement, yielding a success rate of 33.3 percent. Three interrelated problems were identified: institutional problems involving weak structural positioning and limited institutional support; mechanism problems involving divergent party expectations, adversarial orientation of legal representatives, and substantive complexity of copyright disputes; and human resource problems involving limited mediator availability, insufficient copyright-specific competence, and excessive workload. Failed mediations were generally escalated to criminal proceedings, reflecting a tendency to criminalize inherently civil disputes. This study concludes that mediation effectiveness at the regional level remains suboptimal, necessitating institutional strengthening, mechanism improvement, and enhanced mediator competence grounded in intellectual property expertise.